2014
DOI: 10.1111/cpsp.12070
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder in DSM‐5: New criteria and controversies.

Abstract: The fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM‐5; American Psychiatric Association, 2013) featured extensive changes to the posttraumatic stress disorder (PTSD) diagnosis. PTSD was moved out of the anxiety disorders into a new class of “trauma‐ and stressor‐related disorders,” and the definition of what constitutes a traumatic experience was revised. Three new symptoms were added, existing ones were modified, and a new four‐cluster organization and diagnostic algorithm were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 85 publications
0
23
0
1
Order By: Relevance
“…ICD-11 has proposed a substantially different approach to diagnosing PTSD, primarily simplifying the conceptualization of disorder but also distinguishing between basic and complex forms of the condition (Maercker et al, 2013). The dissemination of these proposals has led to important discussions in the field (Miller, Wolf, & Keane, 2014). ICD-11 is scheduled for release in 2018, and in this article we review emerging evidence about the new formulation of PTSD and CPTSD that speaks to whether the proposals are useful in principle and whether revisions of this formulation may be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…ICD-11 has proposed a substantially different approach to diagnosing PTSD, primarily simplifying the conceptualization of disorder but also distinguishing between basic and complex forms of the condition (Maercker et al, 2013). The dissemination of these proposals has led to important discussions in the field (Miller, Wolf, & Keane, 2014). ICD-11 is scheduled for release in 2018, and in this article we review emerging evidence about the new formulation of PTSD and CPTSD that speaks to whether the proposals are useful in principle and whether revisions of this formulation may be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive literature reviews of the dissociative subtype of PTSD can be found elsewhere [79]. Here, we discuss two prominent models of dissociation in PTSD and implications for treatment.…”
mentioning
confidence: 99%
“…Post‐traumatic stress disorder (PTSD) is the most prevalent mental health diagnosis among Veterans enrolled in healthcare at the Department of Veterans Affairs [5]. PTSD is characterized by exposure to a traumatic event followed by a constellation of symptoms, including intrusion symptoms (e.g., memories of the traumatic event), avoidance symptoms (e.g., avoidance of situations that are reminiscent of the traumatic event), negative alterations in cognitions and mood (e.g., persistent emotional negative state), and alterations in arousal and reactivity (e.g., exaggerated startle response) [6]. The negative impact of PTSD on physical and emotional health and interpersonal and occupational functioning has been well documented [7–9].…”
mentioning
confidence: 99%